O crescimento neopentecostal no bairro dos Prazeres: motivos e razões de mudanças de denominação religiosa. - Lemos, Jardson Alves (2010)
Our research concentrates on the study of the increasing phenomenon of the movements contemporary neopentecostal, being taken as reference the neighborhood of the Prazeres and your limitations in the city district of Jaboatão dos Guararapes - Pernambuco, due to the proliferation of churches as IURD, International Church of the Grace of God etc. However we just limited to the first church. We will try to focus the causes of such phenomena, by the traditional churches that lost a significant share of followers for the new pentecostals, the important reasons of such a religious traffic and your processes of conversions